Wild Honey Poisoning: A Case Report from Remote Mountains (Global Journal of Medical Research, 2021)
Wild honey is consumed as a tonic in different parts of the world with a belief of increasing libido and treating various musculoskeletal, gastrointestinal and cardiovascular symptoms. However, honey produced from the nectar of several species of the Ericaceae (Rhododendron) family may contain grayanotoxins which act on sodium ion channels and place them in partially open state which causes symptoms like sweating, dizziness and altered sensorium owing to their effect on cardiac muscles and nervous system. We report a case of 60 years male who consumed wild honey as a pain reliever and later presented to the emergency room of Manang District Hospital with bradycardia, hypotension and altered mental status.
Keywords: wild honey; grayanotoxins